Factors of financial literacy: A study among students in University Malaysia Kelantan (UMK) during pandemic of Covid-19 - Yussapikah Yunos; Zetty Karmila Abd Rafar; Nor Azizah Sa’ri; Wan Amin Khalili Wan Mohd Abrisam (2022)
This study investigates the relationship between Financial Education, Financial Socialization, Personality Characteristic (Financial Attitude and Financial Behavior) and Financial Knowledge towards Financial Literacy among the students in University Malaysia Kelantan during pandemic Covid-19. In brand new surroundings, the potential to deal with personal finances has become increasingly more critical. The people must know about being financially literate because it is important to manage their money well. University students have faced several challenges. Most students having financial problems are alarming these days. Based upon the Theory of Planned Behavior model developed, this research aims to study the factor of financial literacy among students in University Malaysia Kelantan (UMK) during the pandemic of Covid-19. It is conducted to investigate the relationship between financial education, financial socialization, personality characteristics, and financial knowledge with the financial literacy of the student. Based on a quantitative survey and a sample of 152 respondents, data was analyzed using SPSS version 26.0. The result showed Financial Education, Financial Socialization, Personal Characteristics (Financial Attitude and Financial Behavior) and Financial Knowledge have a strong positive impact on financial literacy. The findings support the results from some earlier studies. The findings also have strong positive significant contributions to the advancement of knowledge about financial or money in financial literacy among the students and on behalf of the University Malaysia Kelantan also need to provide economic support. The findings of this study, which indicated that students at the University Malaysia Kelantan (UMK) are competent about division questions. It can be inferred that University Malaysia Kelantan students have a moderate comprehension of diversification and the time value of money. However, this study has potential limitation around study and lacking time and those limitations can be improved in the future research.